2013
DOI: 10.1302/2046-3758.29.2000196
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-fat diet, branched-chain amino acids and exercise on female C57BL/6 mouse Achilles tendon biomechanical properties

Abstract: ObjectivesThe goals of this study were: 1) to determine if high-fat diet (HFD) feeding in female mice would negatively impact biomechanical and histologic consequences on the Achilles tendon and quadriceps muscle; and 2) to investigate whether exercise and branched-chain amino acid (BCAA) supplementation would affect these parameters or attenuate any negative consequences resulting from HFD consumption.MethodsWe examined the effects of 16 weeks of 60% HFD feeding, voluntary exercise (free choice wheel running)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…Total modulus was not reported in that study, but, when trying to calculate this parameter from the data provided (maximum stress divided by maximum strain), there was an 8% decrease in total modulus in obese rats (obese: 938 MPa vs. lean: 1,024 MPa) compared with a 13% decrease in the present study. Supporting these findings, another study also found decreased modulus in the Achilles tendon of mice fed with a HFD (11). In the present study, we found almost similar results, a softening of the tail tendons in HFD mice compared with ND mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Total modulus was not reported in that study, but, when trying to calculate this parameter from the data provided (maximum stress divided by maximum strain), there was an 8% decrease in total modulus in obese rats (obese: 938 MPa vs. lean: 1,024 MPa) compared with a 13% decrease in the present study. Supporting these findings, another study also found decreased modulus in the Achilles tendon of mice fed with a HFD (11). In the present study, we found almost similar results, a softening of the tail tendons in HFD mice compared with ND mice.…”
Section: Discussionsupporting
confidence: 91%
“…The elastic modulus of different hypercholesterolemic animal tendons has been reported to decrease (6) or increase (7); and, furthermore, in mice fed with a high-fat diet (HFD), tendon modulus has been reported to decrease (11), while deformation as well as strain of collagen fibrils have been reported to increase in obese rats (9). Thus the results are not only sparse and conflicting, but most studies are performed on weight-bearing tissue, which makes it difficult to separate the potential influence of metabolic deterioration from that of mechanical loading, especially with increased body weight as in obesity.…”
mentioning
confidence: 99%
“…BCAA supplementation did not significantly affect glucose tolerance (p = 0.93, p = 0.70 for main effect of BCAA at 5 and 15 weeks, respectively). Data at the 10 week time point followed a similar trend to the 5 and 15 week data (Boivin et al, 2013). …”
Section: Resultssupporting
confidence: 61%
“…Instead, we found that voluntary exercise significantly protected against HFD-induced obesity and glucose intolerance, and while BCAA supplementation did not significantly alter glucose tolerance, it did significantly improve lean to fat mass ratio in combination with voluntary exercise. We previously reported the body weight at the end of the study and glucose tolerance after 10 weeks in these same mice, but the focus was on the effects and correlation with Achilles tendon properties (Boivin et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Another study reported an increase in the tendon stiffness and modulus in the supraspinatus tendons of hypercholesterolemic (ApoE -/-) mice compared to control mice [24] , whereas a subsequent study by the same group reported a reduced modulus in the patellar tendons of aging ApoE -/- mice compared to controls [25] . Boivin et al studied the influence of high fat diet on C57Bl/6 female mice, and reported a reduced modulus and increased CSA of the Achilles tendon compared to standard diet [26] . It is possible that the increased CSA observed in the study by Boivin et al (measured at the surface of the tendon with digital calipers) resulted from the deposition of peritendinous fat, which was excluded from our US-based CSA measures.…”
Section: Discussionmentioning
confidence: 99%